Pomen pevskih zborov za skupnost - Rojko, Blaž (Socialno delo, 2015)
Community projects addressing "target groups" mostly miss the needs of a real community, and are therefore not very welcome by the community. To solve this problem it's good to organise the projects in cooperation with the existing communities. The choirs are among such communities. They are important in social work not only as the environment for the community projects, but also as a place where the emerging communal processes and social interactions act as the protective factors for the individual and enable spontaneous collaborative solving of the social problems. In the presented research the values and attitudes of the choir members were ascertained, and the impact of socio-demographic factors on them was explored. Based on the factor analysis, four scales of the attitudes toward the social processes in the choirs were determined. The intergeneration relations, the importance of singing, socializing and social network, and self-affirmation through the choir are the most important concerns for the choir singers. Among others, gender, marital status and employment influence these attitudes. They are also contingent on the choir status. It has been confirmed that besides the cultural organisations the choirs are important autopoetic communities, which can offer support and feeling of identity to their members. As such they are an important environment for the community social work, and therefore some financial resources dedicated for the social security should be invested in them.
Keywords: community social work; skupnostno socialno delo; attitudes; skupnost; pevski zbori; singing; socialni procesi; socio-demographic factors; druženje; socialising